Spatial variability and post-depositional diffusion of stable isotopes in high accumulation regions of East Antarctica - Mahalinganathan, Kanthanathan; Thamban, Meloth; Ejaz, Tariq; Srivastava, Rohit; Redkar, B. L.; Laluraj, C. M. (Frontiers in Earth Science, 2022)
Stable isotopes of Antarcticice cores are used extensively in reconstructing the past climate. Variations in snow accumulation patterns and post-depositional processes such as changes in isotope ratios due to diffusion may complicate these records. We analyzed the spatio-temporal variations of snow accumulation, stable isotopic composition, and factors controlling their distribution along two transects in the Dronning Maud Land (DML) and Princess Elizabeth Land (PEL) regions of East Antarctica. The δ18O and δD variations are dominantly influenced by snow accumulation in the DML region and temperature in the PEL region. To evaluate the extent of diffusion in isotope records, the isotope record of an ice core (IND-33) drilled after 5 years close to the DML transect was compared with the snow isotope records. A quantitative comparison of the snow core δ18O records with that of the ice core revealed signal attenuation ranging between 55 and 70%. Using a firn diffusion model, we estimated a diffusion length of 6 cm in IND-33 over 5 years. Our study revealed that while isotope diffusion exists even in high accumulation sites of coastal Antarctica, it does not significantly impact the dating and paleoclimatic interpretation of isotope records, unlike in low accumulation areas.